The Prevalence and Factors Associated with Metabolic Syndrome in Rheumatoid Arthritis Patients - Rudy Hidayat; Ricky; Dicky L. Tahapary; Hamzah Shatri; RM. Suryo Anggoro; Anna Ariane; Sumariyono (Indonesian Journal of Rheumatology, 2022)
Background: Rheumatoid arthritis (RA) is an independent risk factor of cardiovascular disease (CVD), causing 30-50% mortality in RA patients. Metabolic syndrome is a combination of metabolic disorders that can be manifested as central obesity, impaired blood pressure, or abnormalities of carbohydrate and lipid metabolism, which is closely associated with CVD in RA patients. The prevalence and factors associated with the incidence of metabolic syndrome in RA patients vary in previous studies. This study aimed to determine the prevalence and factors associated with the incidence of metabolic syndrome in RA patients at Cipto Mangunkusumo National Central General Hospital, Jakarta. Methods: A total of 145 RA patients at the Rheumatology Clinic of Cipto Mangunkusumo National Central General Hospital from October to December 2021 were included as research subjects by consecutive sampling method. History taking about the disease and demographic data, physical and anthropometric examination, and laboratory tests were done on the patients. The prevalence of the metabolic syndrome was determined using harmonization criteria. Statistical analysis was performed to determine the association of the variables of age, smoking habit, disease activity, duration of disease, glucocorticoid treatment, and methotrexate treatment with metabolic syndrome in RA patients. Results: The prevalence of metabolic syndrome was 19.3% in RA patients with a mean age of 49.8 ± 11.6 years. The variables of gender, age, deformity, physical activity, extraarticular manifestation, smoking habit, disease activity, disease duration, glucocorticoid treatment, and methotrexate treatment were not statistically significant to the incidence of metabolic syndrome in RA patients. Conclusion: The prevalence of metabolic syndrome in RA patients in this study was 19.3%, and no variable was associated with the prevalence of metabolic syndrome.